Critical development factors in infrastructure for the communications industry based on wholesale leased line services in Taiwan - Shu-Hua Li; Jen-Chieh Chen (International Telecommunications Society (ITS), 2019)
To address the demand for 5G ultra-high transmission rate and high connection density and to provide high quality service in the area, the future mobile telecommunications network will consist of an overlay of millimeter wave capable small cells, marking a strong need for private leased line transmission capacity. First, this study will use UK, Germany, Japan and Australia as benchmark objects: UK and Germany review their leased line market periodically and frequently, having obtained significant progress in the service over the years, with relevant policies and institutions maturely developed; Japan has frequent technical exchange and interaction with Taiwan as the telecommunication development environments in both countries are quite similar due to geographical proximity; and Australia's WEF ranking and GDP are similar to those of Taiwan. With studies on these countries, we may suggest a benchmarking paths for Taiwan's industrial development. As there is a wide development gap among the countries, and no consensus is achieved, consequently all the conditions are not completed. For this reason, primarily the purpose of this study is to analyze the current development situation of leased line in Taiwan's telecommunications industry and explore its competitive profile and, secondly, to examine the national competitive advantage factor combination for the development of local leased line service. Based on the Diamond model, this study is intended to provide a comprehensive understanding of the characteristics of the telecommunication market, identifying the resources and conditions required for developing the industry for a nation. If we simply duplicate approaches while ignoring the characteristics of the industry, we may miss the best timing of growth and lose the effects. Based on the Diamond model by Porter (1990), this study employs a fuzzy analytic hierarchy process (Fuzzy AHP) approach, together with expert questionnaire survey, to examine the weight for each dimension and factor, identifying the most critical dimension for the development of fixed line and private line in Taiwan and factors with less influence on the industrial growth to avoid excessive unnecessary resource. According to the research result, government is identified as the most important critical factor, followed by related and supporting industries, and then the demand. The final weight analysis shows that the national policy, in the "government" dimension, is a significant critical factor, and the pull-through effect of leased line related industries is also great, followed by the market size. Thus, during the growth of the leased line industry, these three conditions serve as supporting factors and are deemed the decisive factor of whether the leased line wholesale service can be successfully incubated and developed.
Keywords: 330